BUM Desa Bersama: Strategi Transformasi Pengelola Kegiatan DBM Eks PNPM Mandiri Pedesaan - Rokim, Mochammad; Wijaya, Mahendra; Setyowati, Retno (LPPM Institut Pendidikan Nusantara Global, 2024)
The aim of this article is to analyze the transformation strategy of the community revolving funds ex national program for rural independent community empowerment (DBM Ex PNPM MPd) into a joint village-owned enterprises (BUM Desa Bersama). The research method in this article is qualitative descriptive research. Data collection was carried out by interviews, observation and documentation. The transformation strategy for the DBM Ex PNPM MPd Program into a BUM Desa Bersama is carried out by (1) Transferring assets, by means of capital participation sourced from 25 villages in Kanor District and sourced from the DBM Ex PNPM MPd. (2) Institutional Transfer, the transfer of a government poverty alleviation and empowerment program, namely UPK Ex PNPM MPd, to a community-owned business entity that has a legal entity and aims to overcome poverty by empowering the community or also called BUM Desa Bersama. (3) Transfer of Personnel by forming a joint BUM Desa organizational structure involving the DBM Ex PNPM MPd Activity Manager by considering the suitability of organizational needs and good governance practices. (4) Transfer of business activities, Community Revolving Fund (DBM) / savings and loan business activities which are UPK DBM Ex PNPM MPd business activities to become the main business activities of the joint BUM Desa Bersama. Apart from that, it also develops other businesses such as the establishment of a PT LKM and participation in the BPJS Employment shield agent.